2008
DOI: 10.1038/nrc2326
|View full text |Cite
|
Sign up to set email alerts
|

DNA vaccines: precision tools for activating effective immunity against cancer

Abstract: DNA vaccination has suddenly become a favoured strategy for inducing immunity. The molecular precision offered by gene-based vaccines, together with the facility to include additional genes to direct and amplify immunity, has always been attractive. However, the apparent failure to translate operational success in preclinical models to the clinic, for reasons that are now rather obvious, reduced initial enthusiasm. Recently, novel delivery systems, especially electroporation, have overcome this translational b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
331
0
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(346 citation statements)
references
References 134 publications
3
331
0
6
Order By: Relevance
“…In addition, it has been suggested that the effector profile and other less well-understood properties of discrete TAA-specific T-cell subpopulations may also have an important role in tumor regression. 24 Thus, in light of our data and additional information generated independently, 25,26 we re-evaluated the strengths and limitations of plasmid-based immunization as an option for active immunotherapy in cancer. More specifically, we sought to integrate the concept of immunization by direct intra-lymph node administration with a plasmid prime/peptide boost approach in an attempt to synergize key features of these two immunizing vectors: (i) plasmid priming for induction of a highquality immune response and (ii) peptide boosting for amplification and functional conversion of the immune response.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been suggested that the effector profile and other less well-understood properties of discrete TAA-specific T-cell subpopulations may also have an important role in tumor regression. 24 Thus, in light of our data and additional information generated independently, 25,26 we re-evaluated the strengths and limitations of plasmid-based immunization as an option for active immunotherapy in cancer. More specifically, we sought to integrate the concept of immunization by direct intra-lymph node administration with a plasmid prime/peptide boost approach in an attempt to synergize key features of these two immunizing vectors: (i) plasmid priming for induction of a highquality immune response and (ii) peptide boosting for amplification and functional conversion of the immune response.…”
Section: Introductionmentioning
confidence: 99%
“…This process results in efficient T-cell priming within secondary lymphatic tissues. [4][5][6][7] Although DNA vaccines have been very successful in inducing antigen-specific immune responses in mice, [8][9][10] immunogenicity in humans and large animals has so far been largely disappointing. 3,9,11 The reasons are diverse, but are mostly related to topics such as dosing, application route, tissue distribution and differences in toll-like receptor (TLR) expression patterns between mice and humans.…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches have been pursued to improve the immunogenicity of DNA vaccines including the coexpression of immunomodulatory molecules such as cytokines and chemokines. 10,[13][14][15][16] Chemokines such as CCR7-ligands Ebstein-Barr-Virus-inducedmolecule-1-ligand-chemokine (ELC/CCL19) and secondary lymphoid-tissue chemokine (SLC/CCL21) are key regulators of innate and adaptive immune responses, since they orchestrate migration of DC and T cells into secondary lymphatic tissues, thereby organizing immune synapse formation. [17][18][19][20] CCL19 is constitutively expressed by cells distributed throughout the T-cell zones of lymph nodes, spleen and Peyer's patches.…”
Section: Introductionmentioning
confidence: 99%
“…The generation of immune responses has been demonstrated to be due to transfection of MHC class 1-expressing bystander cells as well as professional antigen-presenting cells, by direct transfection and via cross-presentation [8]. As a result, plasmid DNA vaccines are able to elicit both CD4+ and CD8+ cellular antigen-specific immunity, a characteristic that sets DNA vaccines apart from many other types of active immunotherapy [9, 10]. In addition, the presence of unmethylated CpG motifs present in the bacterial DNA may further serve as an immune stimulant by TLR9 activation [11].…”
Section: Introduction: Cancer Immunotherapy and Anti-tumor Vaccinesmentioning
confidence: 99%